(untitled) (Ameghiniana, 2013)
"Two new species of the genus Platystrophia are described from the uppermost beds of the San Juan Formation in the Precordillera of Argentina. Conodonts which were obtained from the limestone provided Platystrophia minuta n. sp. and the graptolite fauna found in the overlying Los Azules Formation indicate an Early Ordovician age. The beds of the Talacasto region which contain Platystrophia fasciculata n. sp., are probably slightly younger than strata of the Cerro Viejo region. The occurrence oí the genus Platystrophia in Early Ordovician beds of western Argentina suggests closest paleobiogeographical affinities with both the Celtic and Baltic faunal provinces."